Research on Nanoeffect of Penetration and Consolidation under Nonlinear Characteristics of Saturated Soft Clay - Yu Zhao; Ning Wang; Deying Zhang (International Journal of Analytical Chemistry)
In order to systematically study the nanopermeability properties of saturated soft clay under different consolidation pressures and different osmotic pressures, this paper analyzes various loading and unloading conditions that affect the permeability of soil based on the material description equation with displacement as the control variable of large deformation consolidation theory. By summarizing the empirical relationship between permeability coefficient and consolidation pressure and permeability coefficient and void ratio, the infiltration law and seepage failure characteristics of soft clay are revealed. For the soil studied in this paper, a = 0.65, b = 0.001, and q = 3.55 are acceptable. The effect of the initial permeability coefficient on large deformation consolidation is studied, and the necessity and plausibility of considering the nonlinearity of the compression and permeability coefficient when calculating the soft-land base large deformation consolidation is also studied.